Synergising hydrothermal pre-treatment and biological processes for enhancing biohydrogen production from palm oil mill effluent - Zainal, Bidattul Syirat; Yu, Kai Ling; Ong, Hwai Chyuan; Mohamed, Hassan; Ker, Pin Jern; Abdulkreem-Alsultan, G.; Taufiq-Yap, Yun Hin; Mahlia, TM Indra (Institution of Chemical Engineers, 2024)
The high quantity of nutrient-rich palm oil mill effluent (POME) waste in the industry will have a severe negative environmental impact and a high cost of treatment. However, POME waste could be converted into bioenergy via environmentally sustainable processes. Several studies have explored using hydrothermal carbonisation for solid biomass products in biofuel production, but the potential of the liquid phase produced during these processes has received less attention. Therefore, this study aims to assess the potential of biohydrogen production from treated POME as a substrate by hydrothermal process. This study is presented in two phases: the first phase involves substrate pre-treatment using a hydrothermal process to improve biomass properties at different temperatures, and the second phase explores the potential for biohydrogen production from treated POME through dark fermentation. Substrate pre-treatment was conducted at 180, 210, and 240 °C using 100 % raw POME. Next, the treated POME was incubated for biohydrogen production at 50 °C for 24 h. A microbial analysis was conducted to determine the most dominant species present in the sample. Our findings show that at 180 °C, the total chemical oxygen demand (COD) removal efficiency was 80 %, and acetic acid concentration was 28 %. Compared to raw POME, treated POME generated a maximum hydrogen yield and rate (HPR) of 52.19 mL H2 g−1 CODrem and 0.59 mL H2 mL POME−1 day−1 with a 2.32-fold and 1.59-fold increase, respectively. Meanwhile, Clostridium was a dominant bacterial species identified in the treated POME. These findings demonstrated the feasibility of implementing a hydrothermal process to treat POME and improve its biohydrogen production efficiency. The treated POME from the hydrothermal process is more homogenous and readily consumable by microorganisms used in dark fermentation. Hydrothermal pre-treatment could potentially increase the rate and efficiency of microbial digestion, leading to enhanced hydrogen production. The high COD removal efficiency during the process significantly reduces the environmental impact of POME discharge, and converting POME into a valuable resource through the hydrothermal and dark fermentation process aligns with sustainable waste management practices.